A Comparison of Clinical Outcomes of Two Methods of Femoral Hamstring Graft Pin Fixation in Anterior Cruciate Ligament Reconstruction - Ken Lee Puah MBBS, MRCSEd, M.Med (Ortho Surg); Khai Phang Wong MBBS; William Yeo MPhty; Andrew Hwee Chye Tan MBBS, FRCS (Glas), FRCS Ed (Orth) (Proceedings of Singapore Healthcare, 2013)
The outcome of anterior cruciate ligament (ACL) reconstruction with hamstring grafts depends on early rehabilitation and secure graft fixation. Various devices available for graft fixation at the femoral tunnel have different biomechanical properties as demonstrated on cadaveric studies. The aim of this study was to compare clinical outcomes in patients using either of two methods of transfemoral pin fixation for hamstring grafts in ACL reconstruction. Twenty-eight patients undergoing primary ACL reconstruction with hamstring autograft with either transfemoral expansion fixation (Rigidfix) or cortical-cancellous suspension (Transfix) by a single surgeon were analysed including subjective knee scores and objective measurements including range of motion and arthrometer-measured anterior translation. Transfix was used in 14 (50.0%) patients and Rigidfix was used in 14 (50.0%) patients. There was no significant difference in pre-injury Tegner activity scores, pre-operative Tegner activity scores, Lysholm scores and age or in Tegner post-operative activity scores, Lysholm scores, range of motion, Lachman and pivot scores absolute anterior translation and anterior translation compared to the non-operated knee at two years. There was a significant improvement in Tegner (2.6 ± 2.4, p <0.00) and Lysholm (25.3 ± 21.2, p <0.00) scores at two years with no significant difference between the two groups. One patient had a broken Transfix cross-pin 13 months after surgery which presented as a subcutaneous swelling which was removed. Although the biomechanical properties of Rigidfix and Transfix differ as demonstrated in cadaveric studies, both devices had similar favourable clinical outcomes in our series.